Novel and known MYOC exon 3 mutations in an admixed Peruvian primary open-angle glaucoma population - Mendoza Reinoso, Veronica (2012)
Purpose: The aim of this study was to characterize a representative sample of the Peruvian population suffering openangle glaucoma (OAG) with respect to the myocilin gene (MYOC) mutations, glaucoma phenotype, and ancestry for future glaucoma risk assessment. Methods: DNA samples from 414 unrelated Peruvian subjects, including 205 open-angle glaucoma cases (10 juvenile glaucoma [JOAG], 19 normal-tension glaucoma [NTG], and 176 POAG) and 209 randomly sampled controls, were screened for nucleotide changes in MYOC exon 3 by conformational sensitive gel electrophoresis (CSGE) and mutation screening. Results: We identified a probable causative novel MYOC missense mutation, Gly326Ser, in one POAG case and found a consistent genotype-phenotype correlation in eight of his relatives. We also found the known causative MYOC mutation Trp286Arg in one JOAG case and one POAG case. A known causative single base MYOC deletion, T1357, was found in one POAG case. Two previously reported silent polymorphisms, Thr325Thr and Tyr347Tyr, were found in both the case and the control populations. A novel missense variant, Met476Arg, was identified in two unrelated controls. Conclusions: The screening of exon 3 of MYOC in a representative sample of 205 independent POAG patients from Peru and 209 matched controls identified novel and previously reported mutations (both pathogenic and nonpathogenic) from other global regions. These results reflect the complex admixture of Amerindian and Old World ancestry in urban populations of Latin America, in general, and in Peru, in particular. It will be important to gather information about the ancestral origin of MYOC and other POAG gene mutations to develop screening panels and risk assessment for POAG in Peru.